Níveis de fósforo disponível na dieta de poedeiras - Andre Luiz Costa Machado (2010)
An experiment was carried out in order to evaluate the levels of avaiable phosphorus (aP) in the diets of layers from 18 to 50 weeks, on performance, egg and bone tissue quality. The diets were isonutritious and isoenergetic, except for the levels of aP. The treatments, defined by the levels of avaiable phosphorus in the feed, were A= 0,15; B= 0,25; C= 0,35 e D= 0,45% of aP. The birds were distributed in a completely randomized design, consisting of an experimental unit with four treatments and six replications of 25 birds each. No differences were found (P>0,05) between the treatments for the variables of performance (feed intake, percentage of eggs, number of eggs per hen, egg wheight, viability, and feed: gain ratio per dozen eggs), egg quality (Haugh units, egg percentages of yolk, albumen and shell, and shell resistance), bone tissue quality (Resistance of the bone to breakage and ash percentage) and blood activity of alkaline phosphatase (BAAP). A linear effect was found (P>0,05; R2 = 0,97) for the birds wheight, where the birds that were fed with 0,45% of aP had the biggest weight. There was a quadratic effect (P>0,05; R2 = 0,99) for the Seedors index (indicator of bone density) where the birds that were fed with the biggest level of aP had better bone density. The treatment with less aP (0,15% aP) presented in morfologic analises of the bone medular region the presence of osteomalacia, therefore we can suggest that 0,25% aP in layers diets is ideal. This level of aP was enough to guarantee a good performance and ensure the egg and bone tissue quality.